The impossible - Bayona, J.A.; Watts, Naomi; McGregor, Ewan; Holland, Tom ([place of publication not identified] : [Telecino Cinema], 2012)
Maria, Henry and their three sons begin their winter vacation in Thailand, looking forward to a few days in tropical paradise. But on the morning of December 26th, as the family relaxes around the pool after their Christmas festivities the night before, a terrifying roar rises up from the center of the earth. As Maria freezes in fear, a huge wall of black water races across the hotel grounds toward her.
Director of photography, Oscar Faura ; executive producer, Sandra Hermida, Javier Ugarte ; edited by Elena Ruiz, Bernat Vilaplana.
Naomi Watts, Ewan McGregor, Tom Holland.
LPF: P13
DVD format, Fullscreen (4:3), PAL, Region 3.
In English with optional Chinese, English and Malay subtitles.
Title from disc label.
Keywords: Indian Ocean Tsunami, 2004 -- Phuket -- Thailand -- Drama; Tsunamis -- Drama; Families in motion pictures